The Effects of Reading Aloud Strategies on Text Level Difficulties, Reading Proficiency and Reading Comprehension Skill - Sajid, Muhammad Khalid Mehmood; Hafizoah, Kassim (Universiti Malaysia Pahang, 2019)
Reading aloud is an essential learning strategy that can increase the quality of students’ reading comprehension abilities, which significant role may help them to overcome text level difficulties of the learning materials. This pilot study focused on reading aloud as an appropriate reading strategy for efficient outcomes for low-proficiency Saudi students. Mixed method design was employed with the administration of three research instruments; a reading test, a questionnaire and an interview protocol for teachers and students. Participants were 30 postgraduate students who attended a foundation English course at a public university in Saudi Arabia. The students were put into an experimental group where the reading aloud strategies were applied. The findings showed significant results. The results of the reading test and questionnaire showed that the students did better in the posttest than the pretest. In general, most of the students indicated that reading aloud strategies have helped them to improve their reading proficiency, better understand higher level texts, and hence improve their reading comprehension skill.